A New Stress-Based Model of Political Extremism: Personal Exposure to Terrorism, Psychological Distress, and Exclusionist Political Attitudes - Canetti-Nisim, Daphna (2009)
Does exposure to terrorism lead to hostility toward minorities? Drawing on theories from clinical and social psychology, we propose a stress-based model of political extremism in which psychological distress—which is largely overlooked in political scholarship—and threat perceptions mediate the relationship between exposure to terrorism and attitudes toward minorities. To test the model, a representative sample of 469 Israeli Jewish respondents was interviewed on three occasions at six-month intervals. Structural Equation Modeling indicated that exposure to terrorism predicted psychological distress (t1), which predicted perceived threat from Palestinian citizens of Israel (t2), which, in turn, predicted exclusionist attitudes toward Palestinian citizens of Israel (t3). These findings provide solid evidence and a mechanism for the hypothesis that terrorism introduces nondemocratic attitudes threatening minority rights. It suggests that psychological distress plays an important role in political decision making and should be incorporated in models drawing upon political psychology.